SIMPLE AND RAPID METHOD FOR ISOLATING ANTHOCYANIN FROM WILD MULBERRY (Morus nigra L.) - Rollando Rollando; Christopher Daniel Kurniawan; Ririn Nurdiani; Sophia Yusnita Wahyu Timur; Paulina Genoveva Moza (Sanata Dharma University, 2019)
Wild mulberry (Morus nigra L.) is a kind of berries that has a high content of anthocyanin pigment. Anthocyanin is a natural pigment that has good biological activity so that widely be used as both food and drug ingredients. There are many studies conducted that have isolation anthocyanin from mulberry extract, but most of them used various expensive methods and the process included several steps that make them not cost-effective nor time-efficient. This research was conducted in order to do an isolation of anthocyanin from wild mulberry through a single step. The extraction of compounds was done by maceration and the isolation was done by thin layer chromatography method. The isolation product was identified with reagents, consisting of ferric chloride and sodium hydroxide, and with spectrophotometry methods, consisting of UV-Vis and infrared spectrophotometry. As result, this research was able to isolate anthocyanin from wild mulberry fruit by thin layer chromatography method. The identification with spectrophotometry methods indicated that the isolated compound hypothetically was anthocyanidin-3-O-rutinoside.